Mechanical Properties of Bombyx mori Silk Yarns Studied with Tensile Testing Method - Aksakal, Baki; Tsobkallo, Ekaterina; Darvish, Diana (WILEY, 2009)
The mechanical properties of Bombyx mori silk yarns and baves were investigated with tensile testing method. After silk yarns were pre-extended at different strain levels and fixed for a while followed by recovery process, the tensile characteristics were examined in detail. It was commonly observed that low preliminary extensions up to 2-3% do not cause the changes of the mechanical properties and stress-strain curves because they result in small structural changes and distortions, which were recovered within relatively short time (similar to 1 min) in recovery process. However, pre-extension values >3% strain lead to great changes of the mechanical properties and fibre structure, i.e., the changes of the shape of stress-strain curve where additional transition point was observed, increase in the rigidity and stress at rupture, but decrease in extensibility as a result of orientation and destruction of the fibre structure especially in the amorphous region. It was stated that silk fibre consists of two distinct deformation regions, namely first linear region extending up to 2-3% strain and the second region beyond 2-3%, strain where the main reorganization processes of the fibre structure, that is, the straining of macromolecular chains especially in the amorphous regions, the orientation of structural units such as (beta-sheet microcrystals in stretching direction, and the destruction of macromolecules take place. (C) 2009 Wiley Periodicals, Inc. J Appl Poly in Sci 113: 25142523,2009
Keywords: fibres; mechanical properties; structure-property relations; strain; stress; STRESS-STRAIN; BEHAVIOR; FIBERS; Polymer Science